Smoking in pregnancy: associations with skinfold thickness, maternal weight gain, and fetal size at birth. Issue 6277 (23rd May 1981) - D'Souza, S W; Black, P; Richards, B
Abstract : Skinfold thickness is an index of subcutaneous fat, and certain maternal conditions during pregnancy affect the skinfold thicknesses of the baby. A study was performed to investigate the effect of smoking on skinfold thickness, maternal weight gain, and fetal size at birth. A total of 452 mothers with normal singleton pregnancies were groups as: non-smokers, light-to-moderate smokers, or heavy smokers. Maternal age, height, parity, and duration of pregnancy were similar in the three groups. Heavy smokers gained significantly less weight than non-smokers, but there was no significant difference in skinfold thickness. Babies born to smokers had lower birth weights and smaller head circumferences and were shorter than those born to non-smokers, but skinfold thicknesses were similar. The presence of a normal layer of subcutaneous fat in babies whose mothers smoked suggests that fetal growth retardation is not caused by nutritional deficiencies.